2017
DOI: 10.1016/j.heares.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganization in postlingually deaf cochlear implant users: Intra-modal and cross-modal considerations

Abstract: With the advances of cochlear implant (CI) technology, many deaf individuals can partially regain their hearing ability. However, there is a large variation in the level of recovery. Cortical changes induced by hearing deprivation and restoration with CIs have been thought to contribute to this variation. The current review aims to identify these cortical changes in postlingually deaf CI users and discusses their maladaptive or adaptive relationship to the CI outcome. Overall, intra-modal and cross-modal reorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 75 publications
4
61
0
Order By: Relevance
“…Furthermore, a recent study showed cross-modal reorganization of the visual cortex in CI users (Chen, Sandmann, Thorne, Bleichner, & Debener, 2015). The relationship between the reorganization of visual and auditory cortices in response to auditory sensory deprivation may be linked to speech recognition performance (see Stropahl, Chen, & Debener (2016) for a review). It is therefore important to investigate the integration of information from both modalities to further our understanding of neural changes due to auditory deprivation (and subsequent auditory restoration).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed cross-modal reorganization of the visual cortex in CI users (Chen, Sandmann, Thorne, Bleichner, & Debener, 2015). The relationship between the reorganization of visual and auditory cortices in response to auditory sensory deprivation may be linked to speech recognition performance (see Stropahl, Chen, & Debener (2016) for a review). It is therefore important to investigate the integration of information from both modalities to further our understanding of neural changes due to auditory deprivation (and subsequent auditory restoration).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant N1 latency differences between good and poor CI performers were revealed in the present study. Brain plasticity associated with hearing loss has been suggested to underlie the cortical activation pattern with hearing loss and/or with CI use (Pantev et al, 2006;Stropahl et al, 2017). However, the degree of brain plasticity can be different among CI users depending on demographic factors and environmental influences, including rehabilitation.…”
Section: Am Change As a Paradigm To Assess Cortical Temporal Processimentioning
confidence: 99%
“…Neuroimaging studies of crossmodal plasticity following cochlear implantation have utilized fNIRS (Saliba et al 2016), PET (Strelnikov et al 2015a), and EEG (Sharma et al 2015) to investigate the neural correlates of these visual perceptual enhancements. Here, we will briefly discuss several representative studies from this substantial body of work (for a thorough review of the topic of crossmodal plasticity in CI users, see Anderson et al 2016; Stropahl et al 2016). …”
Section: Cross Modal Plasticity/animal Modelsmentioning
confidence: 99%